2013
DOI: 10.1002/ejsp.1998
|View full text |Cite
|
Sign up to set email alerts
|

Gamers against science: The case of the violent video games debate

Abstract: This article explores the notion that scientific research programs and empirical findings are fundamentally devalued when they threaten a perceiver's social identity. Findings from three studies show the following: (1) identification with the group of “gamers” (i.e., people who play video games on a regular basis) influences the extent to which perceivers devalue research suggesting that playing violent video games has negative consequences; (2) this effect is mediated by the feeling that the group of gamers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 51 publications
(56 reference statements)
8
97
0
Order By: Relevance
“…The researchers concluded that individuals selfidentifying as Republican were not only less predisposed to believe a refutation incongruent with their party's prewar perspective but also doubled-down on the information that was refuted (i.e., intensified their original belief in the erroneous information as a consequence of the attempted correction). Other researchers have observed similar effects for a range of issues, including climate change (Hart & Nisbet, 2012), healthcare reform (Nyhan, Reifler, & Ubel, 2013), video game violence (Nauroth, Gollwitzer, Bender, & Rothmund, 2014, 2015, vaccinations (Nyhan & Reifler, 2015a;Nyhan, Reifler, Richey, & Freed, 2014), water conservation (Seyranian, Sinatra, & Polikoff, 2015), and even Lyme disease (Roh, McComas, Rickard, & Decker, 2015), and have arrived at similar conclusions: Attempts to argue for the inadequacy of incorrect knowledge in these areas results in some individuals more strongly adhering to that knowledge.…”
Section: Backfire Effectmentioning
confidence: 77%
See 1 more Smart Citation
“…The researchers concluded that individuals selfidentifying as Republican were not only less predisposed to believe a refutation incongruent with their party's prewar perspective but also doubled-down on the information that was refuted (i.e., intensified their original belief in the erroneous information as a consequence of the attempted correction). Other researchers have observed similar effects for a range of issues, including climate change (Hart & Nisbet, 2012), healthcare reform (Nyhan, Reifler, & Ubel, 2013), video game violence (Nauroth, Gollwitzer, Bender, & Rothmund, 2014, 2015, vaccinations (Nyhan & Reifler, 2015a;Nyhan, Reifler, Richey, & Freed, 2014), water conservation (Seyranian, Sinatra, & Polikoff, 2015), and even Lyme disease (Roh, McComas, Rickard, & Decker, 2015), and have arrived at similar conclusions: Attempts to argue for the inadequacy of incorrect knowledge in these areas results in some individuals more strongly adhering to that knowledge.…”
Section: Backfire Effectmentioning
confidence: 77%
“…Lewandowsky, Stritzke, Oberauer, & Morales, 2005) and expend effort to counter-argue it (Nauroth et al, 2014(Nauroth et al, , 2015Nyhan & Reifler, 2010;Prasad et al, 2009). In so doing they activate more evidence that supports their original belief.…”
mentioning
confidence: 98%
“…This uncomfortable feeling is called cognitive dissonance (Festinger, 1957), and one way to reduce it is to dismiss the evidence. There is research evidence indicating that this is exactly what "gamers" do when they encounter evidence indicating that violent video games increase aggression (Bender et al, 2013;Nauroth, Gollwitzer, Bender, & Rothmund, 2014;Greitemeyer, 2014). Fifth, people often feel uncomfortable whenever they believe that someone is trying to limit their freedom, such as by restricting media.…”
Section: Consumers Of Violent Media Are Motivated To Deny Violent Medmentioning
confidence: 98%
“…Murray, 1984) an argument some advocates of harm-related hypotheses have revived more recently (e.g. Bushman, Gollwitzer, & Cruz, 2014).…”
Section: No Consensus On a Consensusmentioning
confidence: 99%